Peningkatan Literasi Matematis Melalui Model Problem Based Learning dalam Pembelajaran Teorema Pythagoras - Trilani, Sopi Saniah; Sudihartinih, Eyus; Hasanah, Aan (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
The purpose of this study was to determine the increase in the mathematical literacy skills of junior high school students through the Problem Based Learning model on the Pythagorean theorem material, and to find out students' responses to learning the Pythagorean theorem using the Problem Based Learning model. This type of research is a quantitative research with a quasi-experimental research method. The research design used is the Non-equivalent Control Group Design. The population in this study were class VIII students at one of the public junior high schools in Cimahi City. The research sample consisted of two classes, namely experimental class 1 for class VIII-I using the Problem Based Learning model and experimental class 2, namely class VIII-H using the Discovery Learning model. The research instrument used in this study was a test instrument for students' mathematical literacy abilities, and non-test instruments in the form of questionnaires and interviews. The result of this study is statistically, it is found that the increase in the mathematical literacy ability of students who obtain the Problem Based Learning model is the same as that of students who obtain the Discovery Learning model.